Factores que limitan la productividad del cultivo del frijol en el Departamento de Narino, Colombia - Arcila G., B.; Angulo R., N.F. (International Center for Tropical Agriculture, 1987)
In order to identify factors limiting bean production in Narino, Colombia, meetings were held in different localities with groups of farmers, and later, some of them were surveyed at random. Results are analyzed including land preparation; planting time and distance; fertilizer aplication times, forms, and doses; weeds and ways to control them; diseases; pests; var.; and yields. Farmers in Funes, Yacuanquer, Tangua, and Buesaco plant 2 or 3 var. at the same time to get higher production and better prices. Best yields are obtained by planting in Oct. (450-850 kg/ha). (CIAT)